The podocyte slit diaphragm—from a thin grey line to a complex signalling hub - Grahammer, Florian; Schell, Christoph; Huber, Tobias B. (Nature reviews. Nephrology, 2013)
This article highlights the evolution in understanding of the podocyte slit diaphragm. Now appreciated as far more than a simple intercellular connection, the slit diaphragm controls the structure and function of the glomerular filtration barrier. However, several slit diaphragm properties remain unclear: its role in filtration, exact molecular structure, and the complex pathways initiated by this dynamic signalling hub. The architectural design of our kidneys is amazingly complex, and culminates in the 3D structure of the glomerular filter. During filtration, plasma passes through a sieve consisting of a fenestrated endothelium and a broad basement membrane before it reaches the most unique part, the slit diaphragm, a specialized type of intercellular junction that connects neighbouring podocyte foot processes. When podocytes become stressed, irrespective of the causative stimulus, they undergo foot process effacement and loss of slit diaphragms—two key steps leading to proteinuria. Thus, proteinuria is the unifying denominator of a broad spectrum of podocytopathies. With the rising prevalence of chronic kidney disease and the fact that glomerular diseases account for the majority of patients with end-stage renal disease, further investigation and elucidation of this unique structure is of paramount importance. This Review recounts how perception of the slit diaphragm has changed over time as a result of intense research, from its first anatomical description as a thin intercellular connection, to an appreciation of its role as a dynamic signalling hub. These observations led to the introduction of novel concepts in podocyte biology, which could pave the way to development of highly desired, specific therapeutic strategies for glomerular diseases. Key Points The slit diaphragm is a unique intercellular contact point that integrates the structural components of various other cell junction types, including tight, adhesion, gap and neuronal junctions We propose that the slit diaphragm should be classified as a unique category of intercellular junction Slit diaphragm functioning is impaired in all monogenic inherited proteinuric diseases The slit diaphragm executes several highly specialized functions: macromolecular filtering, connecting the slit diaphragm to the actin cytoskeleton and initiating signalling pathways that regulate the plasticity of foot processes The slit diaphragm also mediates calcium signalling, mechanosensation, regulation of the cytoskeleton, cell polarity, cell survival, endocytosis and transcription Further research into this delicate structure holds the potential to discover novel treatment options for proteinuria and chronic kidney diseases